The Effect of Financial Inclusion on Nigeria’s Real Economic Growth - Obademi, O. E.; Biiranee, K. F. B.; Thomas, Adeyanju (International Journal of Economics and Financial Issues, 2025)
This study investigated the effect of financial inclusion on economic development in Nigeria over the period 1990–2023. Using an ex-post facto research design, secondary data were obtained from the Central Bank of Nigeria (CBN) Statistical Bulletin and the World Development Indicators (WDI). The growth rate of GDP per capita was employed as a proxy for economic development, while financial inclusion was captured through commercial bank loans to rural areas, deposits from rural areas, credits to small and medium-scale enterprises (SMEs), and the number of bank branches in rural areas. Descriptive statistics, unit root tests, the Johansen co-integration approach, and the Error Correction Model (ECM) were employed, with diagnostic tests ensuring the robustness of results. The findings revealed a long-run relationship among the variables, indicating that financial inclusion and economic development move together over time. Specifically, commercial bank loans to rural areas, deposits from rural areas, and SME credits were all found to significantly and positively impact economic growth. The presence of bank branches in rural areas also contributed positively to growth by expanding financial infrastructure and enabling broader access to financial services. These results emphasize that financial inclusion is a critical driver of Nigeria’s economic GROWTH. The study concluded that policies promoting rural lending, deposit mobilization, SME financing, and rural banking infrastructure are vital for inclusive and sustainable growth. It recommended that government and financial institutions design tailored loan schemes for rural communities, strengthen incentives for rural savings, and expand SME credit through credit guarantees and concessional financing. Moreover, expanding banking infrastructure through both physical branches and digital platforms was emphasized as essential for bridging the financial access gap.